Utilization of red dragon fruit peel as an antioxidant in edible film sago starch packing lempok durian - Jeri Irawan; Netti Herawati; Raswen Effendy; Angga Pramana; Maghfirah Jayalaksamana (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Lempok durian is a traditional food product typical of Riau, which in storage often experiences a decrease in quality due to oxidation. The utilization of edible film with the addition of antioxidants form natural source in food products has the potential to protect food products such as lempok durian to be more durable. This study aimed to obtain the best concentration of dragon fruit peel extract in making the edible film of sago starch as Lempok durian packaging. This study was conducted experimentally using a completely randomized design of four treatments, each with four replications to obtain sixteen experimental units. The treatments in this study consisted of P0 = Without the addition of dragon fruit peel extract, P1 = addition of 6% red dragon fruit peel juice, P2 = 8% red dragon fruit peel extract, P3 = Addition of 10% red dragon fruit peel extract. The data obtained were analyzed statistically using Analysis of Variance (ANOVA). If the calculated F is greater than or equal to the F table, the analysis will continue with Duncan's Multiple Range Test (DMRT) further tests at the 5% level. The results of the study concluded that the addition of dragon fruit peel extract with various concentrations had a significant effect on the characteristics of the edible film of sago starch and the storage of the Lempok durian produced, moisture content according to standards, increasing thickness, suppressing the rate of water vapor transmission, increasing antioxidant activity, reducing free fatty acids, and aroma hedonic test. The best formulation in this study was P3 treatment with 15.93% moisture content, 0.22 mm thickness, 6.73 g/m2/hour water vapor transmission, 133.15 ppm antioxidant, free fatty acids on the ninth day of 1.50 %, and the ninth-day hedonic aroma test was 2.86 (somewhat likeTherefore, the utilization of edible film with the addition of natural antioxidants from dragon fruit peel has the potential to be developed into packaging that can prevent rapid oxidation.